2018
DOI: 10.1002/eji.201747295
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immune response to Clostridium difficile infection: A perspective for prevention and therapy

Abstract: Clostridium difficile infection (CDI) is one of the most important nosocomial illnesses and a major cause of morbidity and mortality. While initial treatment of CDI is usually successful, unprovoked relapses remain an important and frustrating problem. This review examines the literature describing the natural immune response to CDI, and to what extent it can explain the propensity for relapses. In particular, we discuss studies on antibody and, to a lesser extent, B cell and T cell responses in CDI. Despite y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…However, disruption of host microbiota, most commonly through antibiotic treatment, results in increased susceptibility to infection. 3,4 Furthermore, 20% of adults over the age of 65 are asymptomatically colonized by C. difficile, which increases the chance of CDI and may act as potential vehicles of transmission in a healthcare setting. 5,6 Several research groups and national programs have surveyed health-care sites and treating physicians, to evaluate incidence, prevalence, infection control practices and economic burden of CDI in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…However, disruption of host microbiota, most commonly through antibiotic treatment, results in increased susceptibility to infection. 3,4 Furthermore, 20% of adults over the age of 65 are asymptomatically colonized by C. difficile, which increases the chance of CDI and may act as potential vehicles of transmission in a healthcare setting. 5,6 Several research groups and national programs have surveyed health-care sites and treating physicians, to evaluate incidence, prevalence, infection control practices and economic burden of CDI in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings described above it can be speculated that an antibiotic-induced IgA-deficiency could account for susceptibility to C. difficile infection (CDI) ( 114 ). High titers of toxin (TcdA and TcdB)-specific antibodies, in particular IgA in serum and feces, correlate with protection against CDI, while low titers or absence of toxin-specific IgG and IgA were found in patients with acute or recurrent CDI and in non-colonized individuals ( 115 118 ). These data indicated that patients with transient deficiency in IgA might be more susceptible for infection.…”
Section: Microbiological and Immunological Susceptibility To mentioning
confidence: 99%
“…Clostridioides difficile infections (CDI) afflict nearly half a million patients in the United States on an annual basis, and have progressively increased in incidence as well as severity in recent years. These infections lead to the death of 29,000 patients in the United States annually, most of whom are elderly (1, 2). While typically regarded a hospital acquired entity, the epidemiology of CDI has shifted in the past decade and half the cases are now community acquired among low risk populations (3).…”
Section: Introductionmentioning
confidence: 99%
“…The development of specific serum antibodies in response to ongoing CDI is well recognized (14, 18). However, the utility of measuring the antibody response is confounded by the sub-population of patients who carry serum antibodies consequent to environmental exposure and subclinical infection (2, 19, 20). Further, the increase in serum anti-CD antibody levels may occur well into the infectious course, typically in the second week following symptom onset (21).…”
Section: Introductionmentioning
confidence: 99%